Desenvolvimento e avaliação de filmes didáticos no processo de ensino-aprendizagem de química no ensino médio - Teixeira, Francisco Márcio Barbosa (2006)
This research aimed at analyzing the computer’s indirect usage in the Chemistry teaching-learning process in high school. For such a purpose, two short pedagogical films (SPF), which contained images captured by digital camera and images produced by graphic design, were produced; it was studied as well the transmission of the audio that was added to the films during the edition’s period, such as narration, for instance. The usage of the films occurred through a mini course given to two different groups of students. There were two teams in the first group; the duration of this mini course was of a week, totalizing twenty hours. The second group was divided into three teams according to the students’ degree of scholarship in high school; it took three weeks, with four hours and a half of mini course to each team. It was also adopted a sequence of research during the application of these films: (1) the usage of an initial questionnaire about the topic to be studied, i.e.: the material physical properties; the chemical relationships; and the chemical equilibrium; (2) the introduction of the contents through a practical class with materials and experiences directly related to the topic; (3) the usage of the first film; (4) the formal presentation of the contents; (5) the usage of the second film; (6) and the application of a final questionnaire. It was possible to observe the assimilation of the showed contents by some of the students when both questionnaires were compared. The first group of students who took part of the mini course classes had better results of learning. The second team did not have so satisfactory results as the first one, perhaps because the time of the application period was not enough. At last, it was pointed out an optimized sequence to the production of SPF, close to those of this research